The Effect of Financial Compensation, Non-Financial Compensation, and Leadership Style on Employees Performance at PT Arindo Jaya Mandiri - Safira Umul K; Dody - Setyadi; Mellasanti - Ayuwardani (Politeknik Negeri Semarang, 2021)
This study aims to determine respondents' perceptions of financial compensation, non-financial compensation, and leadership style on the employees performance of PT Arindo Jaya Mandiri . This study uses a quantitative approach and uses a sample of 34 employees. The data collection method used in this research was distribute the questionnaire, interview, and literature review. While the analysis technique uses multiple linear regression analysis which is equipped with classical assumption test, t test, f test, and coefficient of determination using SPSS 24 software. The regression equation is Y = 4,646 + 0,432X1-0,73X2 + 0,45X3. The coefficient of determination (R2) is 64,6%. The results of this study indicate that financial compensation (X1) has a significantly positive effect on employee performance (Y), non-financial compensation (X2) has a significantly negative effect on employee performance (Y), and leadership style (X3) hasn’t a significantly effect on performance. employees (Y). The results show that financial compensation, non-financial compensation, and leadership style have a joint and significant effect on employee performance.